The Effect of Polyunsaturated Fatty Acids Omega-3 Supplementation on the Components of Rheumatoid Arthritis Disease Activity: A Systematic Literature Review - Nadia Hidayat; Awalia Awalia; Betty Agustina Tambunan; Hermina Novida (Indonesian Rheumatology Association, 2022)
Background: Rheumatoid arthritis (AR) is a chronic disease that causes deformity in most productive age and can lead to death as disease activity increases. Omega-3 polyunsaturated fatty acids (PUFAs) have the potential to complement available therapies in reducing disease activity. Currently, the effect of omega-3 PUFAs on disease activity components is still unclear. This study aimed to determine the effect of omega-3 PUFAs’ supplementation on the components of RA disease activity. Methods: This research is a systematic study with PRISMA guidelines. Literature identification using Pubmed, MDPI, and clinicaltrials.gov. The inclusion criteria used were: giving omega-3 PUFAs, free full-text, RCT, in English or Indonesian, and assessing disease activity and its components; while the exclusion criteria were: unpublished, comparisons were inappropriate. Assessment of literature quality with the Cochrane Collaboration tool. Results: The study included six studies from 1994 to 2017. The effect of omega-3 PUFAs is diversity in changes of disease activity in 4 of 5 studies. Another effect is a significant reduction in the number of joint pains in the literature by daily doses above 2.9 grams or at lower doses taking longer, and swollen joints in 2 studies that were only affected in doses above 2.9 grams. Another change is a significant reduction in pain severity in the studies. Change increases with higher doses. There are variable LED and CRP changes with minimal study resources. Conclusion: Omega-3 PUFAs depend on their dose and administration duration and can, directly and indirectly, affect disease activity through the influence of most of its components, namely: the number of joints affected, the degree of pain, but the results of the ESR and CRP examinations are not sufficient.